CAT Community Program Faculty Guide 2012 - Kansas State University, K-State First (Kansas State University. K-State First., 2012)
A guide for faculty and staff members teaching Connecting Across Topics (CAT) Communities. Provides an overview of all K-State First programs, as well as specific guidelines and suggestions for in-class activities, co-curricular events, and how best to incorporate student Learning Assistants into the teaching and learning process.
Keywords: Guide; CAT communities; Faculty development; First-year experience program; Learning Assistants; Living-learning communities; Brochures